Association between risky dietary behaviors and academic achievement among adolescent girls: a cross-sectional study in Surabaya, Indonesia - Tatarini Ika Pipitcahyani; Ervi Husni; Dina Isfentiani; Nina Primasari; Halimatus Sa'diyah; Mohammad Zamroni (International Journal of Public Health Science (IJPHS), 2026)
Risky dieting is an unbalanced eating pattern increasingly practiced by adolescent girls and has the potential to impact cognitive function and academic achievement. However, previous research has focused more on the impact of risky dieting on nutritional status and physical health, while empirical evidence regarding its relationship with academic achievement in adolescent girls is still limited, particularly in the context of higher education. This study aimed to analyze the relationship between risky dieting and academic achievement in adolescent girls. The study used a quantitative design involving 70 adolescent girls. Data were collected through a peer counselor-based questionnaire to measure risky dietary habits and academic achievement. Data analysis was performed using Fisher's exact test. The results showed p-values of 0.05 and 0.023, respectively, indicating a significant relationship between risky dieting and academic achievement. Adolescent girls who engaged in risky dieting tended to have lower semester GPAs (11%) and cumulative GPAs (4%). The study concluded that risky dieting contributes to decreased academic achievement. This study contributes by expanding empirical evidence regarding the impact of risky dieting on academic achievement and emphasizes the importance of integrating nutrition interventions and health education in strategies to improve academic achievement in adolescent girls.